2007
DOI: 10.1007/s10517-007-0392-4
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of allogenic cells in the therapy of patients with dilated cardiomyopathy

Abstract: We carried out a pilot study on intracoronary transplantation of prenatal allogenic skeletal myoblasts and multipotent bone marrow stromal cells to patients with dilated cardiomyopathy. Intracoronary transplantation of allogenic cells is a feasible and safe procedure: there were no life-threatening rhythm and conduction disturbances, symptoms of hemodynamic instability, and thromboembolic complications. Positive clinical effect of cell transplantation persisted for 6 months and consisted in decreased content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A benefit from cell therapies is corroborated by many studies where clinical or functional improvement has been reported [6] . At the same time, there is a gap between advertising and a more fundamental part of the scientific literature: the former speaks about rejuvenation of tissues etc., and the latter explains sometimes questionable therapeutic effects by paracrine or immunomodulating mechanisms via secretion of cytokines or growth factors [5,7] .…”
mentioning
confidence: 85%
“…A benefit from cell therapies is corroborated by many studies where clinical or functional improvement has been reported [6] . At the same time, there is a gap between advertising and a more fundamental part of the scientific literature: the former speaks about rejuvenation of tissues etc., and the latter explains sometimes questionable therapeutic effects by paracrine or immunomodulating mechanisms via secretion of cytokines or growth factors [5,7] .…”
mentioning
confidence: 85%
“…No similar reports have been found in the international literature. Finally, intravenous injections of stem cells to Tb patients should be mentioned together with the warning against unjustified use of Bs for such purposes as it has previously been done concerning intracoronary injections of cells obtained from the abortion material [108][109][110][111][112].…”
Section: Repeated Hemoptysis or Secondary Infectionmentioning
confidence: 99%
“…15 Finally, a clinical study limited to one patient presenting with idiopathic DCM reported improved cardiac function and increased incidence of arrythmias upon injection of autologous Mb at the time of mitral valvuloplasty. 42 In the present study, we used the D7LNB1 cells as our source of Mb for practical and conceptual reasons. Because of their clonal origin, the D7LNB1 cells are purely myogenic, and the preparations do not present the heterogeneity and variability encountered in primary cell cultures.…”
Section: Mb Transplantation In Dcmmentioning
confidence: 99%